Overlapping Powers in Merah Putih Cabinet: Case of Presidential Special Representative - Roisa Nur Hanifah; Ratna Affifah Fatin; Niken Ayu Melani (Journal of Transformative Governance and Social Justice, 2025)
This research discusses the complexity of jurisdiction surrounding the status of the Presidential Special Representative (PSR) in the Red and White Cabinet, as regulated by Presidential Regulation No. 137 of 2024. This examines indications of overlapping authority granted to the Special Presidential Representative (PSR) over several ministries, which has implications for inefficiency in governance. PSR holds an equal position and financial rights comparable to ministers, with the only difference being that PSR does not receive a pension. The emergence of the PSR position has also drawn public criticism, with many assuming that this position is not urgent to establish and could actually complicate the bureaucracy further. This study aims to explore the implications of the PSR role on government efficiency and identify overlaps in key areas such as food security, religious harmony, and small business development, which fall within the scope of several ministries and agencies. This aims to provide insights into how this overlap affects bureaucratic functions, policy implementation, and public perception of government efficiency. Using a literature review methodology, this study observes and analyzes the role of PSR in relation to the existing functions of ministries and evaluates its impact on bureaucratic performance. This study reveals a significant overlap in the assignment of PSR with existing government bodies, resulting in inefficiencies, delays in policy implementation, and public criticism regarding budget waste. The divided opinions of the public and policymakers indicate that the clear mandate of PSR is questionable, whether it is to improve executive performance or complicate the government structure. These findings highlight the need to further evaluate of the PSR’s role to simplify responsibilities and reduce structural complexity within Indonesia’s governance system, with the hope of restoring public trust in government accountability and transparency. Future studies using in-depth observational methods can provide solutions to improve the effectiveness and efficiency of the government structure, both PSR and other government administrative units, which will ultimately enhance the delivery of public services in Indonesia quickly and accurately.